Monitorowanie studenckich umiejetnosci informacyjnych w pedagogicznych instytucjach szkolnictwa wyzszego w Polsce i na Ukrainie - Shevchuk, Lesya (Kultura-Społeczeństwo-Edukacja, 2012)
The article deals with the development of students’ information proficiency in the Polish Republic and Ukraine. The article is devoted to the implications brought into the process of teachers training by the impact of key competencies and information technologies. Special attention is paid to information proficiency and future teachers’ skills that are the most important for their training and perspective career. Monitoring of future teachers’ information proficiency forming at Polish establishments of higher education has been carried out which resulted in developing methodology recommendations for raising the level of the students’ information pro ciency at Ukrainian pedagogical higher educational establishments. Level of scienti fic development of the issue of future teachers’ information pro ciency forming has been described. Competence approach to training teachers for information society has been paid attention to. Peculiarities and structure of future teachers’ information pro ciency have been characterized. Standards and criteria of Polish teachers have been systematized, contents of future teachers’ information proficiency forming at Polish establishments of higher education have been analysed; projects and programmes as means for future teachers’ information proficiency forming have been characterized.